AUTOMATED DESIGN SYSTEM (ADS) - WHAT IS IT, TYPES OF AUTOMATED DESIGN SYSTEMS - Kazakov Firdavs Farxod ugli (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In this article we will tell you what ADS is and what it is used for in work. It is known that technological progress does not stand still. Paper drawings have been replaced by computer-aided design systems - a set of software and hardware designed to automate various stages of development